2017
DOI: 10.20944/preprints201705.0026.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative and Qualitative Analysis of Editor Behavior through maybe Coercive Citations

Abstract: How much is the h-index of an editor of a well ranked journal improved due to citations which occur after his/her appointment? Scientific recognition within academia is widely measured nowadays by the number of citations or h-index. Our dataset is based on a sample of four editors from a well ranked journal (impact factor -IF -greater than 2). The target group consists of two editors who seem to benefit by their position through an increased citation number (and subsequently h-index) within journal. The total … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Editors will have widely varying expectations depending on prior experience (or lack thereof) with library and/ or commercial publisher. Herteliu et al (2017) observed that editors have the ability to influence the hindex of authors. According to Bogdanovic (2003), the quality of journals rests, to a large degree, on the quality of peer review process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Editors will have widely varying expectations depending on prior experience (or lack thereof) with library and/ or commercial publisher. Herteliu et al (2017) observed that editors have the ability to influence the hindex of authors. According to Bogdanovic (2003), the quality of journals rests, to a large degree, on the quality of peer review process.…”
Section: Literature Reviewmentioning
confidence: 99%